The Effect of Mentoring on Undergraduate Mentors: A Systematic Review of the Literature - Leavitt, Andrew S.; Nelson, Kari L.; Cutucache, Christine E. (Frontiers in Education, 2022)
Multiple meta-analyses and systematic reviews have been conducted to evaluate methodological rigor in research on the effect that mentoring has on the mentee. However, little reliable information exists regarding the effect of mentoring on the mentor. As such, we conducted a systematic review of the literature focused on such an effect (if any) within the fields of science, technology, engineering, and mathematics (STEM), aiming to better understand the quality of the research that has been conducted. We focused on undergraduate or post-secondary students as mentors for near-peers and/or youth. This review functions to identify commonalities and disparities of the mentoring program and research components and further promote methodological rigor on the subject by providing a more consistent description of the metrics utilized across studies. We analyzed articles from 2013 to 2020 to determine the features of undergraduate mentor programs and research, the methodological rigor of research applied, and compared them to prior research of this nature. In total, 80 eligible articles were identified through Cronbach’s UTOS framework and evaluated. Our key findings were that nearly all studies employed non-experimental designs, most with solely qualitative measurements and all lacked a full description of program components and/or experimental design, including theoretical framework. Overall, we identified the following best practice suggestions for future research on the effect of mentoring on mentors, specifically: the employment of longitudinal and exploratory mixed methods designs, utilizing sequential collection, and experimental descriptions nested within a theoretical framework.